Linguistic Representation of the Concept of Sun in the Linguoculture of the Peoples of the North (Based on the Yakut and Yukaghir Languages) - Margarita P. Lukina (Гуманитарный вектор, 2021)
The object of the research is the concept of the sun: in the Yakut language ‒ kүn, in the tundra Yukagir language ‒ yerpeye and in the forest Yukaghir language ‒ yeloodye. The article deals with lexical representatives and stable phrases; the motivating, conceptual, figurative features and derivational paradigms of the studied concept are established; applied etymological analysis of words, cognitive approach and conceptual methods of concept research. The concept of the sun is presented in different ways in the linguistic picture of the world of peoples. The description and explanation of the peculiarities of the concept of the sun in the national linguistic picture of the world of the Sakha and Yukaghir people in a comparative-comparative plan seems relevant for conceptual linguistics. As a result of the study, only positive signs of the concept of the sun were noted in both linguocultures. The scope of the linguistic representation of the concept of kүn in the Yakut language is diverse, while the content level is characterized by different options. A large number of derivative words with the lexeme kүn in the Yakut language indicate the cultural significance of this concept. Since ancient times, the Sakha people and the Yukaghirs had a cult of the main heavenly body of the sun, which continues to the present day. The Sakha and Yukaghir people celebrate the Ysyakh and Shahadyibe holidays on the summer solstice, marking the beginning of a new annual cycle. During the holiday, abundance, peace, harmony and love are demonstrated to the main deity, the sun, thereby asking the sun for well-being for the coming year. Thus, the sun is a key concept for these northern peoples.